The humble electrocardiogram. Issue 1 (29th January 2008) - Marsh, Eleanor; O'Callaghan, Peter; Smith, Philip
Abstract : Many patients with potentially life-threatening cardiac conditions presenting with transient loss of consciousness are referred first to neurology clinics. Therefore, neurologists must remain competent to interpret electrocardiograms (ECGs) and in particular be able to identify those rare conditions that predict sudden cardiac death. A 12-lead ECG is cheap and readily available, and can give essential diagnostic information. Here the authors review abnormalities in, and indications for, the ECG in neurological practice.